The Structure of Dense Gas in Perseus and Serpens: CLASSy Results - Mundy, Lee G. (2014)
We present results of a dendrogram analysis of N2H+ J=1-0 data cubes from the CARMA Large Area Star-formation Survey (CLASSy). Dendrogram tree structures are characterized by their morphology and kinematics relative to one another, and provide a useful mechanism for analyzing the hierarchy of molecular regions from core-to-cloud spatial scales. Our CARMA data, with 7" spatial and 0.15 km/sec velocity resolution, yield the following results: (1) trees are more hierarchical in regions of high star formation activity; (2) in all regions, the leaf and branch morphology is widely varying and mostly not circularly symmetric; (3) there is evidence for multiple velocity components along a line of sight in only a small fraction of the mapped areas. We compare the identified N2H+ dendrogram tree structures to Herschel maps of dust emission and to Spitzeridentified young stellar object distributions to compare the dense gas distribution to the current star formation activity.